Evaluasi Kinerja Lalu Lintas Akibat Pembangunan Landmark Simpang Tak Bersinyal Menggunakan PKJI 2023 dan PTV Vissim - Hari Kurniawan; Ida Farida (Jurnal Konstruksi, 2026)
The construction of a landmark at an unsignalized intersection can affect traffic capacity and performance. This study aims to evaluate the impact of the construction of the AS-202 Bravo Aircraft Monument on traffic performance at the Kadungora Three-Leg Intersection, Garut Regency, and to examine handling scenarios through traffic management. The analysis was conducted under three conditions: before the construction of the monument, after the construction of the monument, and after the implementation of opening the divider on the C-leg lane, which previously restricted the new road lane toward Garut. Data were obtained through vehicle flow surveys conducted on weekdays and weekends during peak hours, as well as secondary data from the Transportation Agency. The evaluation refers to PKJI 2023 and includes traffic flow simulation using PTV Vissim Student Version software. The results show that after the monument construction, intersection capacity decreased from 3,086.24 pcu/hour to 3,030 pcu/hour, the degree of saturation increased, and average delay rose, causing the level of service to decline from category C to D. Vissim simulations also indicate increased delay and queue length. The implementation of opening the divider on the C-leg was able to reduce delays and shorten queue lengths. These findings confirm that simple traffic engineering–based interventions can improve intersection performance without major geometric changes. The study recommends maximum intervention in the form of traffic management based on simple engineering measures that can be replicated at similar unsignalized intersections.